2013
DOI: 10.1116/1.4792068
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of metal oxide layers grown on CVD graphene

Abstract: Growth of a fully oxidized aluminum oxide layer with low surface roughness on graphene grown by chemical vapor deposition is demonstrated. This is accomplished by the deposition of a 0.2 nm thick titanium seed layer on the graphene prior to the deposition of the aluminum under ultra high vacuum conditions, which was subsequently oxidized. The stoichiometry and surface roughness of the oxide layers were measured for a range of titanium and aluminum depositions utilizing ex situ x-ray photoelectron spectrometry … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…For this reason, a thin metal seed layer was evaporated on graphene. Titanium was chosen as the seed layer due to its high adsorption energy on graphene 27 and low surface diffusion 28 . The 2 nm film of titanium was oxidized once exposed to air, resulting in a thin layer of TiO 2 on the graphene surface.…”
Section: Resultsmentioning
confidence: 99%
“…For this reason, a thin metal seed layer was evaporated on graphene. Titanium was chosen as the seed layer due to its high adsorption energy on graphene 27 and low surface diffusion 28 . The 2 nm film of titanium was oxidized once exposed to air, resulting in a thin layer of TiO 2 on the graphene surface.…”
Section: Resultsmentioning
confidence: 99%
“…In the scope of previous studies on the chlorination and fluorination of graphene, , our work suggests that p–d hybridization from metal adsorbents could also serve as a valid possibility. In addition, by combining lithography techniques, this new metal-functionalization of graphene and the crystallinity of the titanium surface structure may even serve as a patterned growth template for the preparation of future nanomaterials …”
Section: Discussionmentioning
confidence: 99%
“…[19][20][21] We recently demonstrated that yttria monolayers wet graphene 22 and thus yttria may be an ideal dielectric for graphene devices. This is in agreement with previous use of yttria for graphene or carbon nanotube device structures.…”
Section: Introductionmentioning
confidence: 99%